Exchange rate volatility and oil prices shocks and its impact on economic sustainability - Khuram Shaf; Liu Hua; Zahra Idrees (Management Science Letters)
Impact of exchange rate volatility has received a great attention from the last century, its importance is certain in all sectors of the economy and it affects welfare as well as social life of the economy. Exchange rate between two currencies tells the value of one currency in terms of others one. Depreciation/Appreciation of exchange rate affects economic growth in terms of trade and shifts income to/from exporting countries from/to importing countries. The factors affecting exchange rate are inflation, interest rate, foreign direct investment, government consumption expenditure and balance of trade. This research study examines the impact of oil prices and exchange rate volatility on economic growth in Germany based on 40-year annual data. Cointegration technique is applied to check the impact of macroeconomic variables on exchange rate in the long run and short run. It is estimated that imports, exports, inflation, interest rate, government consumption expenditure and foreign direct investment had significant impacts on real effective exchange rate in the long run and short run. Sin addition, Engle Granger results indicate that relationship was significant for the long run and its error correction adjustment mechanism (ECM) in short a run is significant and correctly signed for Germany.